Electric discharge in the transverse air flow at atmospheric pressure - Prysiazhnevych, I.V.; Martysh, Eu.V.; Lisitchenko, T.E. (Вопросы атомной науки и техники, 2012)
Physical features of the transverse arc discharge and its atmospheric pressure plasma were investigated for the different gas flow rates (gas flow velocity ~ 0…2/3 of the sound speed) and character of the gas flow (laminar/turbulent). Component composition of the plasmaforming gas; electronic excitation temperatures Te* of atoms, vibrational Tv * and rotational Tr* temperatures of molecules in the generated plasma were determined by optical emission spectroscopy. Founded difference of the temperatures Tе*(Cu)>Tе*(O, H) was explained by the additional mechanism of the population of the excited electronic states of cooper atoms (material of electrodes) due to the ion-ion recombination, which is almost absent for the blowing gas atoms. Non-monotonic character of the Tr*(N₂) and Tr*(N₂₊) dependence on the gas flow was connected with transition from laminar to the turbulent gas flow regime. It was shown that at large gas flows (at which the deviation from laminar flow occurs and the turbulence starts) plasma of TA becomes more isothermal. Физические особенности поперечного дугового разряда и его атмосферной плазмы исследованы для различных воздушных потоков (скорости потока ~ 0…2/3 скорости звука) и режимов газовых течений (ламинарного, турбулентного). Состав плазмообразующего газа, электронные температуры заселения Te*атомов, колебательная Tv* и вращательная Tr* температуры заселения молекул в генерируемой плазме определены с помощью оптической эмиссионной спектроскопии. Выявленное отличие между температурами Tе*(Cu)>Tе*(O, H) объяснили дополнительным механизмом заселения возбужденных электронных уровней атомов меди (материал электродов) за счет ион-ионной рекомбинации, который практически отсутствует для атомов обдувающего газа. Немонотонный характер зависимостей Tr*(N₂) и Tr*(N₂₊) от величины газового потока связан с переходом течения газа из ламинарного в турбулентный режим. Показано, что при больших газовых потоках (при которых начинается отклонение от ламинарного режима и появление турбулентности) плазма поперечной дуги становится более изотермичной. Фізичні особливості поперечного дугового розряду та його атмосферної плазми досліджено для різних повітряних потоків (швидкість потоку ~ 0…2/3 швидкості звуку) і режимів газових течій (ламінарної, турбулентної). Склад плазмоутворюючого газу, електронні температури заселення Te* атомів, коливальна Tv* і обертальна Tr* температури заселення молекул у генерованій плазмі визначені за допомогою оптичної емісійної спектроскопії. Виявлену відмінність між температурами Tе*(Cu)>Tе*(O, H) пояснено додатковим механізмом заселення збуджених електронних рівнів атомів міді (матеріал електродів) за рахунок іон-іонної рекомбінації, який практично відсутній для атомів газу, що обдуває дугу. Немонотонний характер залежностей Tr*(N₂) і Tr*(N₂₊) від величини газового потоку пов’язаний з переходом течії газу з ламінарного у турбулентний режим. Показано, що при великих газових потоках (при яких починається відхилення від ламінарного режиму та поява турбулентності) плазма поперечної дуги стає більш ізотермічною.